Kandungan Kapsaisin dalam Kultivar Capsicum annum - Selamat, Jinap; Daud, Mahat (1990)
Thirteen cultivars of chilli Capsicum annum were used for the determination of capsaicin obtained from two stages of maturation, 25 and 40 days after flowering. The results showed that there was a significant difference (p > 0.05) in the capsaicin content among different cultivars for both stages. The range of capsaicin concentration for day 25 was 6.14 - 26.6 mg/g and 6.3 - 106.42 mg/g (dry weight) for day 40. Except for KA2 dan Abheim, other cultivars contained significantly higher concentration of capsiasin in day 40 compared to those in day 25. The range of capsaicin located in the placenta, the pericarp and the seeds was 47 - 60%, 27 - 41 %, 6 - 16%, respectively.